2022
DOI: 10.6028/nist.tn.2228-upd1
|View full text |Cite
|
Sign up to set email alerts
|

Wind-driven fire spread to a structure from fences and mulch

Abstract: A series of field experiments was conducted to examine the effects on fire spread toward a structure for combustible fences and mulch under conditions that may be encountered in a wildland-urban interface (WUI) fire. The fire behavior of a variety of materials, designs, and configurations were studied under various wind conditions. The 187 experiments were split into five categories: mulch only, fence only, fence plus mulch, parallel fences, and long range firebrand experiments. Fence materials included wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 51 publications
(82 reference statements)
1
16
0
Order By: Relevance
“…The firewood pile was located away from the wall of the structure by separation distances ranging from 0.91 m (3 ft) to 7.32 m (24 ft). This range was in contrast to the 0 m (0 ft) to 1.83 m (6 ft) range examined in the fence/mulch study [1]. To study the potential for firebrands to ignite the structure, a target pan of mixed hardwood mulch was positioned at the base of the structure wall.…”
Section: Experimental Designmentioning
confidence: 99%
See 4 more Smart Citations
“…The firewood pile was located away from the wall of the structure by separation distances ranging from 0.91 m (3 ft) to 7.32 m (24 ft). This range was in contrast to the 0 m (0 ft) to 1.83 m (6 ft) range examined in the fence/mulch study [1]. To study the potential for firebrands to ignite the structure, a target pan of mixed hardwood mulch was positioned at the base of the structure wall.…”
Section: Experimental Designmentioning
confidence: 99%
“…Nevertheless, woodpiles do share the firebrand generation aspect of other landscape combustibles such as those mentioned above. The recent NIST study on fences [1] found that: 1. a combustible ground cover such as mulch can generate many firebrands that ignite downwind spot fires and 2. when combined with fences, firebrand production was enhanced. The report [1] listed prior studies of fences and mulch.…”
Section: Landscape Feature Fire Studiesmentioning
confidence: 99%
See 3 more Smart Citations